PHYSIOLOGICAL RESPONSES AND ADAPTATIONS TO TAEKWONDO TRAINING. A SYSTEMATIC REVIEW - Carazo Vargas, Pedro (2013)
This review is proposed in order to analyze the main responses and physiological adaptations that are associated with the practice of taekwondo, assessing the development of knowledge in this area and guidance to coaches and athletes about the most appropriate training processes. A systematic search of databases was performed: "Academic Search Complete, ERIC, Medline, SportDiscus, Proquest, and Ovid." They take into account only research published in scientific journals and only variables that were analyzed in at least five studies are included. This requirement was fulfilled for strength (regardless of its manifestation), aerobic capacity, heart rate and blood lactate production. Twenty-eight publications contributed their findings to this literature review.There is not enough consistency in the evidence developed in order to establish trends in the volume and intensity of appropriate workloads to guide the training process of a taekwondo practitioner, whether for competitive or health purposes. The methodological design of the research conducted in the area should be improved.